Characteristics and Perspectives of Highly Skilled Graduates in the Italian Labour Market - Losurdo, Francesco; Dileo, Ivano; Pereiro, Tha`ıs Garcia (Olsztyn Economic Journal, 2013)
The central aim of this paper is to examine the relationships and implications of the education-employment nexus for recent university graduates in Italy by analysing the main elements that influence college graduates’ employment probabilities three years after graduation. In addition, it provides a comparison among Italian macro-areas regarding graduates’ region of residence in 2010. In this sample, continuous work experience during undergraduate studies, further postgraduate studies, older graduation ages and being married or divorced are characteristics that increase the probability of being employed compared to being unemployed three years after graduation. We used micro-data from a nation-wide survey carried out by the Italian Institute of Statistics (ISTAT) in 2011 on a representative sample of 33,696 graduates belonging to the 2007 cohort. The results confirmed the existence of significant differences in graduates’ employment among Italian macro-areas. Graduates who were employed in the South in 2010 have shown a strong marked profile that is unfavorable to women and is distinguished by the oldest ages of graduates at the time of graduation and in post-graduation pursuits.